2018
DOI: 10.1007/s13668-018-0222-5
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Diet in Preventing Neurodegenerative Diseases

Abstract: Most, but not all, epidemiologic studies report a protective association between MD adherence, cognitive impairment, and brain health. Data from clinical trials supporting these observational findings are also emerging. Limited evidence suggests that MD adherence may be protective for Parkinson's disease risk. Mechanistically, plant polyphenols may activate similar molecular pathways as caloric restriction diets, which helps explain the neuroprotective properties of the MD. Evidence for cognitive disorders is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(54 citation statements)
references
References 98 publications
2
52
0
Order By: Relevance
“…The relationships between greater adherence to these diets and better cognition, slower cognitive decline and decreased risk for dementia could not always be replicated (e.g., e.g., [20][21][22]). Methodological challenges such as the sensitivity of outcome measures, the most sensitive time periods in life course and the true adherence of cultural diverse populations to the predefined diets might have contributed to these inconsistent findings [23]. A complementary strategy for the analysis of dietary patterns is a bottom-up approach, using data-driven methodologies to identify underlying dietary patterns of the specific population under study [24].…”
Section: Introductionmentioning
confidence: 99%
“…The relationships between greater adherence to these diets and better cognition, slower cognitive decline and decreased risk for dementia could not always be replicated (e.g., e.g., [20][21][22]). Methodological challenges such as the sensitivity of outcome measures, the most sensitive time periods in life course and the true adherence of cultural diverse populations to the predefined diets might have contributed to these inconsistent findings [23]. A complementary strategy for the analysis of dietary patterns is a bottom-up approach, using data-driven methodologies to identify underlying dietary patterns of the specific population under study [24].…”
Section: Introductionmentioning
confidence: 99%
“…A number of clinical, epidemiological and experimental studies have suggested that the MedDiet or some of its components may reduce the incidence of neurodegenerative diseases and other conditions related to oxidative stress and chronic inflammation such as cardiovascular diseases (CVD), which are closely associated with cognitive decline (3,4) . These effects can be partially attributed to different bioactive compounds present in the MedDiet such as polyphenols.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, diet interventions and specifically the adherence to Mediterranean diet (MD) have been demonstrated to be a favorable condition, highly associated with the prevention of neurodegenerative disorders [11,12]. This can be explained by the high proportion in this diet of fruits, vegetables, and olive oil, sources of several polyphenolic bioactive compounds [13].…”
Section: Introductionmentioning
confidence: 99%